Rural Marketing: A Case Study On Hindustan Unilever Limited - Kaur, Manpreet (iJARS group, 2013)
In recent years, rural markets have acquired significance, as the overall growth of the economy has resulted into substantial increase in the purchasing power of the rural communities. On account of green revolution, the rural areas are consuming a large quantity of industrial and urban manufactured products. In this context, a special marketing strategy, namely, rural marketing has emerged. This paper is an attempt to find out the various initiatives taken by HUL to reach the rural consumer. Hindustan Unilever is the pioneer and largest player in India’s FMCG market. HUL was the first company to step into the Indian rural marketing. HUL started its first effort towards going rural 1960’s onwards, through indirect coverage of accessible rural market through its urban network stockists and distributors. HUL proactively engaged in rural development in 1976 with Integrated Rural Development Programme in Etah district of Uttar Pradesh. In 1990, HUL launched ‘Operation Streamline’ for distribution of products to inaccessible rural markets with High potential using unconventional transport like bullock carts, tractors and bicycles and appointed rural distributors and star sellers. In 2000, HUL started Project Shakti to reach inaccessible low potential rural markets. This project has reached 100,000 villages. HUL embarked upon Project Samuriddhi in 2003 to create sustainable villages in Dadra and Nagar Haveli. Today HUL’s products touch the lives o f two out of every three Indians